2023
DOI: 10.1021/jacs.3c04335
|View full text |Cite
|
Sign up to set email alerts
|

A Terminal Yttrium Phosphinidene

Abstract: Terminal, nondirectional ionic "multiple" bond interactions between group 15 elements and rare-earth metals (Ln) have remained a challenging target until present. Although reports on terminal imide species have accumulated in the meantime, examples of terminal congeners with the higher homologue phosphorus are yet elusive. Herein, we present the synthesis of the first terminal yttrium organophosphinidene complex, Tp tBu,Me Y(� PC 6 H 3 iPr 2 -2,6)(DMAP) 2 , according to a double-deprotonation sequence previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 90 publications
1
7
0
Order By: Relevance
“…Recent years have witnessed major progress in the field of rare-earth-metal (Ln) complexes with multiply bonded (dianionic) main-group ligands, most notably (organo)imide chemistry. 1–3 Upon closer inspection this is not all that surprising, since [LnNR] moieties display a favourable Pearson hard/hard match and enhanced steric/electronic variability through the imido substituent R, 4 compared to other fragments such as [LnO], 5 [LnPR], 6 or [Ln=CR 2 ]. 7 Of particular interest have been the synthesis of terminal rare-earth-metal imides 8–15 and a fundamental understanding of the Ln–imido bonding as well as reactivity, 16 and in particular small-molecule-activation scenarios.…”
Section: Introductionmentioning
confidence: 95%
“…Recent years have witnessed major progress in the field of rare-earth-metal (Ln) complexes with multiply bonded (dianionic) main-group ligands, most notably (organo)imide chemistry. 1–3 Upon closer inspection this is not all that surprising, since [LnNR] moieties display a favourable Pearson hard/hard match and enhanced steric/electronic variability through the imido substituent R, 4 compared to other fragments such as [LnO], 5 [LnPR], 6 or [Ln=CR 2 ]. 7 Of particular interest have been the synthesis of terminal rare-earth-metal imides 8–15 and a fundamental understanding of the Ln–imido bonding as well as reactivity, 16 and in particular small-molecule-activation scenarios.…”
Section: Introductionmentioning
confidence: 95%
“…Very recently, Sirsch, Anwander and co-workers reported the synthesis and molecular structure of the first terminal yttrium phosphinidene complex, Scheme 13. 61 The reactions of H 2 PDipp with the lanthanide dimethyl complexes [Ln(Tp t Bu,Me )(Me) 2 ] (Ln = Y, Dy, Ho; Tp t Bu,Me = HB(2-Me-4- t Bu-N 2 C 3 H) 3 ) afforded the corresponding phosphide complexes [(Tp t Bu,Me )Ln(Me)(HPDipp)] ( 38Ln , Ln = Y, Dy, Ho). Addition of DMAP to 38Ln gave the corresponding DMAP adducts [(Tp t Bu,Me )Ln(Me)(HPDipp)(DMAP)] ( 39Ln , Ln = Y, Dy, Ho); addition of a further equivalent of DMAP to 38Y produced [Y(Tp t Bu,Me )(PDipp)(DMAP) 2 ] ( 40 ).…”
Section: Lanthanide Phosphorus Complexesmentioning
confidence: 99%
“…More recently, Roesky and co-workers found that yellow arsenic (As 4 ) is also a useful source to introduce polyarsenic ligands to lanthanides. Due to the unstable nature of this As 4 allotrope under ambient conditions, the authors used freshly-prepared As 4 in solution to react with the divalent precursor [Sm(DippForm) 2 (THF) 2 ]; after workup, red crystals of the cyclo -As 4 complex [{Sm(DippForm) 2 } 2 (μ-η 4 :η 4 -As 4 )] (93), 61 Scheme 29 , were obtained as a minor product, which is essentially isostructural to the lanthanide cyclo -P 4 complex 48. Unfortunately, the presence of non-removable impurities hampered further characterisation on 93 because of the instability of As 4 in solution.…”
Section: Lanthanide Heavier Pnictogen Complexesmentioning
confidence: 99%
“…But with the strong interest in this field, we can expect that the terminal phosphinidene complexes of other rare-earth metals will appear shortly as what we have witnessed in the chemistry of the terminal rare-earth metal imido complexes . Interestingly, after we submitted this Account, Anwander and co-workers reported an yttrium terminal phosphinidene complex . We can also expect more interesting stoichiometric reactivity and catalytic reactivity when the library of the rare-earth metal phosphinidene complexes continues to grow.…”
Section: Discussionmentioning
confidence: 91%